2017
DOI: 10.1097/mph.0000000000000658
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Proteinuria in β-Thalassemia Major Patients With and Without Diabetes Mellitus Taking Deferasirox

Abstract: The results of our study showed that consumption of deferasirox is safe, as there was no significant relationship between spot urine protein/creatinine ratio in diabetic and nondiabetic group. Deferasirox consumption is not associated with increased proteinuria in diabetic patients compared with nondiabetic group having only a transient proteinuria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…On the other hand, a retrospective study of 72 patients (mean age: 20.3 ± 0.9 yrs; 36 male, 36 female) with thalassemia major or intermedia treated at Sultan Qaboos University Hospital found that the renal side effects related to deferasirox appear to be higher than those reported in published clinical trials [92]. Reassuringly, DFX proved to be safe in managing iron overload in thalassemia patients with end stage renal disease [93] or diabetes mellitus [94]. DFO chelates iron is located in plasma and ferritin by forming a metabolically inactive complex, which is renally excreted.…”
Section: The Role Of Iron Chelating Agents In Renal Diseasementioning
confidence: 97%
“…On the other hand, a retrospective study of 72 patients (mean age: 20.3 ± 0.9 yrs; 36 male, 36 female) with thalassemia major or intermedia treated at Sultan Qaboos University Hospital found that the renal side effects related to deferasirox appear to be higher than those reported in published clinical trials [92]. Reassuringly, DFX proved to be safe in managing iron overload in thalassemia patients with end stage renal disease [93] or diabetes mellitus [94]. DFO chelates iron is located in plasma and ferritin by forming a metabolically inactive complex, which is renally excreted.…”
Section: The Role Of Iron Chelating Agents In Renal Diseasementioning
confidence: 97%
“…Studies indicated that ICT did not provide substantial improvements in quality of life, but that the economic burden of long-term treatment with ICT was high. Patients also continued to experience endocrine dysfunction despite lifelong treatment with ICT [ 17 , 19 , 20 , 25 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…showed that DFX (Exjade®) had no significant effects on BUN level in patients compared to the control group. [ 31 ] Karimi et al . [ 31 ] and Aftab et al .…”
Section: Discussionmentioning
confidence: 99%
“…[ 31 ] Karimi et al . [ 31 ] and Aftab et al . [ 25 ] reported that DFX is a safe and effective drug for TM patients.…”
Section: Discussionmentioning
confidence: 99%